Ischemic Preconditioning Increases the Tolerance of Fatty Liver to Hepatic Ischemia-Reperfusion Injury in the Rat - Serafín, Anna (American Society for Investigative Pathology, 2002)
Hepatic steatosis is a major risk factor in ischemia-reperfusion. The present study evaluates whether preconditioning, demonstrated to be effective in normal livers, could also confer protection in the presence of steatosis and investigates the potential underlying protective mechanisms. Fatty rats had increased hepatic injury and decreased survival after 60 minutes of ischemia compared with lean rats. Fatty livers showed a degree of neutrophil accumulation and microcirculatory alterations similar to that of normal livers. However, in presence of steatosis, an increased lipid peroxidation that could be reduced with glutathione-ester pretreatment was observed after hepatic reperfusion. Ischemic preconditioning reduced hepatic injury and increased animal survival. Both in normal and fatty livers, this endogenous protective mechanism was found to control lipid peroxidation, hepatic microcirculation failure, and neutrophil accumulation, reducing the subsequent hepatic injury. These beneficial effects could be mediated by nitric oxide, because the inhibition of nitric oxide synthesis and nitric oxide donor pretreatment abolished and simulated, respectively, the benefits of preconditioning. Thus, ischemic preconditioning could be an effective surgical strategy to reduce the hepatic ischemia-reperfusion injury in normal and fatty livers under normothermic conditions, including hepatic resections, and liver transplantation.